AUDIO VISUAL GEOGRAPHIES: FROM BEYOND THE GEOGRAPHIES OF CINEMA: para além das Geografias de Cinema - Moreira, Tiago de Almeida (2012)
The paper makes a review and a critical analyzes by a new area of the geographic researches that has been presented as Geographies of Cinema. By this review the author proposes a new and more abridgment area of geographic researches, the Audio Visual Geographies, that includes not only the Geographies of Cinema, but also the geographic analyzes of television productions, of the propaganda, of the animations, of the video games and others. That new area proposed pretend open the possibility of geographic analyzes and didactic use of the audio visual language in all of your forms.